Fab fragments of ovine antibody to colchicine enhance its clearance in the rat. (June 2015) - Peake, Philip W.; Pianta, Timothy J.; Succar, Lena; Fernando, Mangalee; Buckley, Nicholas A.; Endre, Zoltan H.
Abstract: Context . Colchicine is an anti-inflammatory alkaloid used for the treatment of acute gout, but has a narrow therapeutic index. Colchicine overdoses are relatively rare, but have high mortality requiring rapid treatment. Objective . To evaluate the ability of a newly available ovine fragment antigen-binding (Fab) antibody to colchicine (ColchiFab ™ ) to protect rats against renal and other injury 24 h after colchicine ingestion. Materials and methods . Rats were gavaged with colchicine (5 mg/kg), then 2 h later injected intraperitoneally with 5 ml of sterile saline, or Fab anti-colchicine, a newly available ovine antibody to colchicine. Samples of blood were taken at 1, 2, 5 and 24 h after gavage, and urine was collected from 5 to 24 h after gavage. Concentrations of colchicine in tissue, blood and urine were measured by liquid chromatography/mass spectrometry, concentrations of Fab anti-colchicine, urinary neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 or KIM-1 by enzyme-linked immunosorbent assay or ELISA, while concentrations of creatine kinase and creatinine (Cr) were measured enzymatically. Results . Colchicine equilibrated rapidly throughout the body and increased serum creatine kinase. Fab anti-colchicine also rapidly redistributed to the blood and remained at high concentrations over 24 h. Fab anti-colchicine caused a rapid 7.1-fold increase in serum colchicine level, followed by excretion of both colchicine and Fab anti-colchicine through the urine. This was associated with the accumulation of colchicine in the kidney, a reversal of colchicine-induced diarrhoea, and increasing urinary NGAL level; from 168 ± 48 to 477 ± 255 ng/mmol Cr [mean ± standard deviation or SD]. Discussion . Fab anti-colchicine greatly increased the clearance of colchicine, although increasing NGAL level suggested the presence of mild kidney damage. Conclusion . These data suggest clinical utility for Fab anti-colchicine in the treatment of colchicine overdose.